2012
DOI: 10.1038/nn.3241
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of visual channels in the inner retina

Abstract: Bipolar cells (BCs) form parallel channels that carry visual signals from the outer to the inner retina. Each BC type is thought to carry a distinct visual message to select types of amacrine cells (ACs) and ganglion cells (GCs). However, the number of GC types exceeds that of BCs providing their input, suggesting that BC signals diversify on transmission to GCs. Here we explored in the salamander retina how signals from individual BCs feed into multiple GCs, and found that each BC could evoke distinct respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 56 publications
(120 reference statements)
10
99
0
Order By: Relevance
“…Second, because the number of DSGC types is thought to exceed that of the BC types providing their input (Vaney et al 2012), some local regions of the BC axon terminal are expected to function autonomously, so that they can selectively synapse onto multiple types of DSGCs with different preferred directions. This type of compartmentalized axonal computation would mirror the dendritic computation occurring in the postsynaptic SAC dendrites (Euler et al 2002;Fried et al 2002Fried et al , 2005Hausselt et al 2007; Lee et al 2010; Lee and Zhou 2006;Yonehara et al 2011) and would be consistent with a recent study that shows that a single BC can send different signals to different ganglion cells (Asari and Meister 2012). However, because BC terminals that ramify in the SAC and DSGC strata are anatomically compact, it must be tested directly whether these terminals actually have the electrotonic structure to support compartmentalized computation.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Second, because the number of DSGC types is thought to exceed that of the BC types providing their input (Vaney et al 2012), some local regions of the BC axon terminal are expected to function autonomously, so that they can selectively synapse onto multiple types of DSGCs with different preferred directions. This type of compartmentalized axonal computation would mirror the dendritic computation occurring in the postsynaptic SAC dendrites (Euler et al 2002;Fried et al 2002Fried et al , 2005Hausselt et al 2007; Lee et al 2010; Lee and Zhou 2006;Yonehara et al 2011) and would be consistent with a recent study that shows that a single BC can send different signals to different ganglion cells (Asari and Meister 2012). However, because BC terminals that ramify in the SAC and DSGC strata are anatomically compact, it must be tested directly whether these terminals actually have the electrotonic structure to support compartmentalized computation.…”
supporting
confidence: 80%
“…BC axon terminals are generally thought to be electronically compact because of their limited physical size. However, a recent study found that some BCs in the salamander retina can send distinct signals to different target ganglion cells, raising the possibility of compartmentalized computation in BC axon terminals (Asari and Meister 2012). We now tested this possibility in mouse CB5 cells by comparing the kinetics and relative amplitude of Ca 2ϩ signals from various regions of the axonal arbor.…”
Section: Discussionmentioning
confidence: 96%
“…It will be important to examine whether potential differences in electrical coupling (Cohen and Sterling, 1990) or synaptic nonlinearities (Asari and Meister, 2012) impact the integrative properties of networks of ON cone bipolar cells providing input to distinct postsynaptic targets. Within this context, it is interesting to note we observed stronger supralinear paired bar responses for excitatory inputs to ON-T versus ON-S RGCs (peak NLI=1.25±0.17 (n=5) vs. 0.79±0.07 (n=19), respectively; p=0.01, t-test) and this difference in nonlinear integration was correlated with apparent differences in synaptic transmission between the populations of bipolar cells providing presynaptic input to these RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonlinear transformation of visual signals by bipolar cell synapses has previously been identified as a key step in retinal computation (Asari and Meister, 2012; Baccus et al, 2008; Chang and He, 2014; Demb et al, 2001; Grimes et al, 2014; Grimes et al, 2015). Here, we tested the hypothesis that the gap-junction mediated lateral spread of signals across bipolar cell pathways upstream of this synaptic nonlinearity could enhance retinal sensitivity to visual inputs that elicit overlapping lateral and feed-forward signals within the bipolar network.…”
Section: Introductionmentioning
confidence: 99%
“…Diversity in temporal channels between bipolar synapses also has been demonstrated using optical imaging in the fish retina (Odermatt et al 2012). Interestingly, a recent study of salamander retina suggests that a single bipolar cell might provide temporally distinct outputs to different ganglion cell types (Asari & Meister 2012). …”
Section: Parallel Excitatory Pathways Are Established At the First Rementioning
confidence: 99%